Immunosensor Incorporating Anti-His (C-term) IgG F(ab’) Fragments Attached to Gold Nanorods for Detection of His-Tagged Proteins in Culture Medium - Michal Wąsowicz; Małgorzata Milner; Dorota Radecka; Krystyna Grzelak; Hanna Radecka (Sensors, 2010)
Immunosensors based on gold electrodes (electrochemical) or gold discs (optical) modified with 1,6-hexanedithiol, gold nanorods and Anti-His (C-term) monoclonal antibody F(ab’) fragment are described. The antigen detected by the sensing platform is a recombinant histidine-tagged silk proteinase inhibitor (rSPI2-His6). Electrochemical impedance spectroscopy (EIS) and surface plasmon resonance (SPR) techniques were used as methods for detection of the antigen. This approach allows to detect the antigen protein in concentration of 10 pg per mL (0.13 pM) of culture medium. The immunosensor shows good reproducibility due to covalent immobilization of F(ab’) fragments to gold nanorods layer